NILAI PENDIDIKAN ISLAM DAN PERSPEKTIF KI HAJAR DEWANTARA DALAM TRADISI MANTU KUCING DI PURWOREJO - Naila Salsabilla; M Fahmi Maulana; Siti Khurota A’yunin (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This study aims to analyze Ki Hajar Dewantara’s perspective on the Mantu Kucing tradition in Purworejo Village, Pacitan Subdistrict, Pacitan Regency; to examine the process of conducting this traditional ceremony; and to identify the role of Islamic education in shaping the community’s understanding of this tradition. This study employs a qualitative approach using descriptive methods. Data collection techniques include interviews, observations, and documentation, involving community leaders, religious figures, and village officials as research informants. Research findings indicate that the residents of Purworejo Village view the Mantu Kucing tradition as a cultural practice aimed at invoking rain during prolonged dry seasons. This tradition is carried out in several stages, including village deliberations, preparation of ritual paraphernalia, and a procession featuring two cats treated as a bride and groom, accompanied by various traditional arts. The implementation of this tradition involves collective community participation, thereby fostering values of togetherness, mutual cooperation, and social solidarity. From Ki Hajar Dewantara’s perspective, the Mantu Kucing tradition can be understood as a form of culture-based education that takes place informally within the community and aligns with the concept of the Tri Pusat Pendidikan. Additionally, Islamic education plays a role in shaping the community’s understanding that this tradition is a cultural symbol accompanied by prayers to Allah SWT. The values of monotheism, patience, tawakkal, and social solidarity are reflected in the practice of this tradition. Thus, the Mantu Kucing tradition functions not only as a cultural ritual but also as a medium for social and religious education that contributes to the character development of the community and the preservation of local culture.